Community Knowledge: Local Wisdom in Folk Handicrafts of Barahom Community in Pattani - Auksornnit, Virintorn; Pitagsalee, Chanda; Atthasongkrow, Montakan; Kaewprathom, Songtham; Thammakirati, Mukda; Hnoothong, Kachonpong (Journal of Information and Learning [JIL], 2023)
The present research study aims to identify the local knowledge on folk handicrafts of the Barahom Community in Pattani, Thailand and to examine the practices by which the local knowledge on folk handicrafts is managed and passed on. It deployed qualitative research methodology. The data involved academic documents, observations, interviews, and information media, which were analyzed and synthesized using qualitative thematic analysis. The present study found that the local scholars who are knowledgeable members of the community are models of local knowledge. The local scholars create the knowledge through (1) strengthening community participation, (2) teaching and learning the handicraft skills, (3) systemic managing of the local available resources, (4) promoting the local culture, (5) developing awareness and appreciation of the Barahom community, and (6) creating shared values on Barahom ethics and beliefs.In specific, the variety of the subsequent and preserved local scholars’ knowledge and skills in Barahom folk handicrafts, formed both socially and individually, are deep-rooted and distinct. The local knowledge and skills include both traditional and new and are passed on to generations. Furthermore, the new knowledge and skills formed are drawn from traditional knowledge but with integration of advanced technology. They are managed by classifying them into traditional, new knowledge, or new knowledge drawn from the traditional one. These types of knowledge and skills are developed through community learning and discussions as well as informal conversations and conferences among community members. These interactions lead to the creation of vital knowledge such as local knowledge management, cultural and folk practices, community leaders, and local resources that can be applied and furthered in the future.